Apoptosis induced by Magnolia Grandiora extract in chlorambucil-resistant B-chronic lymphocytic leukemia cells - Marín, Gustavo Horacio (2010)
Background: B-cell chronic lymphocitic leukemia (B-CLL) still remains as an uncurable disease. Even the newest antineoplastic agents have demonstrated limitations in their efficacy. For this reason, further research of new compounds must be done. New pharmacological properties can be obtained from a great diversity botanical species. Among these products, Magnolia Grandiflora receives our attention since it mainly contains Honokiol which had demonstrated effect against B-CLL cells activating different cell death pathways. Aim: To test the ability of Magnolia Grandiflora extracts to induce apoptosis of B-CLL cells in vitro. Materials and Methods: Herb′s extraction: Twenty grams of powdered material were submitted to three consecutives decoctions with 500 ml of distilled water (96 C), filtered and followed by ultrafiltration with cellulose membrane, lyophilized and reconstituted in AIM-V medium at a final concentration of 10 mg/ml solution. B-CLL chlorambucil- resistant cells were separated and cultivated in the presence of Magnolia′s extract. Samples of cells were taken from the cultures at 24, 48 and 72 h for apoptosis analysis by flow cytometry measuring positive annexin V (0.1 g/ml) cells. Statistics: Apoptosis values were represented by the mean plus or minus SD ( SD) for five independent experiments. Statistical significance was determined by Student′s t -test. A P value of 0.05 or less was considered as significant. Results and Conclusion: This article discusses the apoptosis properties of Magnolia on B-CLL cells. The evidence suggests a potentially effective repertoire for B-CLL treatment. This herb extract might have promising therapy strategies in treating B-CLL or other hematological disease resistant to alkylating agents in clinical practice.